Penyuluhan Masyarakat terhadap Penyakit Kusta dalam Upaya Mencegah Disabilitas pada Warga Kwaron di Kelurahan Bangetayu Kulon, Kota Semarang - Meki Pranata; Abdur Rosyid (Jurnal Surya Masyarakat, 2022)
Leprosy is an infectious infectious disease that can be acute and chronic caused by Mycobacterium leprae which is obligate intracellular. Lack of knowledge resulted in the lack of information on leprosy. The public's ignorance about early detection and prevention of leprosy causes the number of people with leprosy to increase. This community service aims to increase public knowledge about leprosy and motivate people to maintain a clean and healthy lifestyle. The method used in community service is conducting counseling through interactive zoom meetings so that the material presented can be directly accepted by the community. The conclusions obtained from this activity include that the community can feel the benefits by increasing knowledge about leprosy and the community strongly agrees as much as 77.78% and agrees as much as 22.22% when counseling activities.